Lignin-chitosan-based biocomposite film for the localized delivery of TLR7 agonist imiquimod - Aashna Jassal; Khushboo Pathania; Pankaj Kumar; Deepender Kaushik; Simran Dhingra; Deepak B. Salunke; Sandip V. Pawar (SpringerOpen, 2024)
Abstract Background As the leading form of non-melanoma skin cancer, basal cell carcinoma (BCC) presents a considerable challenge to healthcare systems, owing to its widespread occurrence. Current treatment options, such as surgical excision, cryotherapy, and localized therapies like imiquimod or 5-fluorouracil, face challenges, especially in designing drug delivery systems that provide prolonged therapeutic effects. This study aims to develop bio-composite polymeric films for localized drug delivery using natural polymers, lignin, and chitosan, to enhance the delivery of the TLR7 agonist imiquimod for BCC treatment. Results The optimized biofilms were prepared by adjusting the polymer ratio and drying techniques to achieve a balanced composition for localized imiquimod delivery. FTIR and DSC characterization confirmed successful drug incorporation into the biofilms, while microscopic studies revealed the biofilms homogeneity and fibrous nature. Drug release studies demonstrated pH-dependent kinetics, with higher release rates at neutral pH. The biofilms exhibited slow and sustained drug release, promising prolonged therapeutic effects. Additionally, the biofilms were non-hemolytic, showed significant antioxidant activity, and demonstrated selective cytotoxicity against B16-F10 mouse skin melanoma cells. Conclusions This study suggests that lignin-chitosan-based imiquimod-loaded biofilms hold potential as an effective topical treatment for BCC. The biofilm's ability to provide sustained drug release, along with their biocompatibility and selective cytotoxicity, indicates a promising approach to enhancing BCC therapy. Graphical abstract